Studi Evaluatif Kebijakan Madrasah Diniyah Takmiliyah Terintegrasi (MDTT) di SD Negeri Suryodiningratan 2 Yogyakarta - Nurul Aisyah (Attractive : Innovative Education Journal, 2024)
This research aims to find out the reasons for policy actors (policy formulators), in this case the Ministry of Religion of Yogyakarta City, to initiate a policy regarding MDTT, what is the process of implementing and evaluating the MDTT policy at Suryodiningratan State Elementary School. This research uses an evaluative qualitative research approach. The type of research is evaluative using the CIPP Model (Context, Input, Process, Product) from Stufflebeam. The research results obtained show that the reason the Ministry of Religion of Yogyakarta City formulated a policy regarding MDTT was due to concerns about students in State Elementary Schools whose level of ability to Read and Write the Al-Qur'an (BTAQ) was low, in terms of technical matters in the field holding a PKS (Cooperation Agreement) with the Yogyakarta City Education Department. The implementation of MDTT at SD Negeri Suryodiningratan 2 involves the school and Honorary Religious Counselors (PAH) as MDTT teaching staff as a whole so that the implementation process of planning, implementation and evaluation activities can run well. Meanwhile, for the MDTT policy evaluation results using the CIPP evaluation model, the results were (+ + + +). These results illustrate that the context component works effectively, the input component is adequate and well fulfilled, the process component also runs well with cooperation between the parties involved, and the product component also produces significant changes related to religious knowledge in students. So, based on the findings of the research results above using CIPP, it can be concluded that the MDTT policy is quite effective